Psicomotricidad y desarrollo del esquema corporal en niños de cinco años en la Institución Educativa Inicial Pública N° 279 Inmaculada Concepción Flor de Punga Requena 2021 - Fachin Alvarado, Jenifer Minerva (2023)
The general objective of the research was to relate psychomotricity and the development of the body schema in five-year-old children at the Public Initial Educational Institution No. 279 Inmaculada Concepción in the town of Flor de Punga in the province of Requena in 2020. For this purpose, the type of relational research was used as a methodology, adopting the non-experimental, field, bivariate and cross-sectional design. The population was made up of 40 children of Initial Education and the sample was census. The observation technique and two questionnaire guides were used to obtain the data. The instruments were the development of the body schema in five-year-old children at the Public Initial Educational Institution No. 279 Inmaculada Concepción. Which means that the higher the level of psychomotricity, the greater the body development in children.